스마트웨어 및 스마트의류에 대한 국내 미디어의 인식 분석: 가능성과 한계점을 중심으로 - 이기현; 김태훈; 이주연; 윤정민 (시스템엔지니어링학술지, 2024)
This study aimed to analyze the social perception of smart wear and smart clothing in South Korea by examining news data from 1990 to 2023 using the BIGKinds platform. Through keyword analysis and time-series analysis, the study investigated trends in media coverage and public interest regarding these technologies. Results indicated that smart wear garnered increasing attention from 2014 to 2016, particularly in healthcare, fitness, and sports, highlighting their utility in health monitoring and adaptive functionalities. Smart clothing, though less covered, also showed potential in healthcare and fitness, providing real-time monitoring of biometric signals. However, challenges such as durability, cost, and user experience issues were identified as barriers to broader adoption. Despite promising applications in personalized healthcare and sports performance, issues like high prices, limited durability, and privacy concerns may hinder widespread acceptance. This study contributes to understanding public awareness and social discourse surrounding smart wear and smart clothing in Korea, offering insights into the technical and social challenges these technologies face. Future research should focus on enhancing cost-effectiveness, user comfort, and data security to improve adoption and integrate these technologies into everyday life.
Keywords: Smart wear; Smart clothing; BIGKinds; Possibilities; Limitation